Anthropometric Comparative Study of Nasal Morphology between Malaysian and Indonesian Populations - Muhammad Khairie Basjuri; Anita Zara Weinheimer; Eddy Saputra Rohmatul Amin; Muhammad Jefri Mohd Yusof (Indonesian Journal of Legal and Forensic Sciences, 2024)
Nasal morphology is one of the most crucial anthropometric characteristics of the human face. Furthermore, the nose is a pivotal feature in constructing a biological profile. In this cross-sectional study, we examined the nasal morphology of 103 Malaysian and 109 Indonesians, totaling 212 individuals from both groups. A comprehensive analysis involved the measurement of 12 nasal morphological features. The statistical tool employed for the analysis was a t-test, which revealed significant differences in various parameters between Malaysians and Indonesians (p<0.05). These findings demonstrate the statistical importance of nasal morphology in discerning racial and ethnic differences. This research suggests that nose measurements could be instrumental in resolving identity mysteries, making them valuable for forensic examination.